Effects of Motivation Interviewing and Self-Management Support Program on Behaviors for Delaying the Progression of Chronic Kidney Disease and Blood Pressure in Persons with Uncontrolled Hypertension - Sukjong, Ruthaichanok; Boonyasopun, Umaporn; Jittanoon, Piyanuch (Nursing Research and Innovation Journal, 2021)
This quasi–experimental, the one group pretest posttest-design with repeated measures, aimed to examine the effects of a motivation interviewing and self-management support program on behaviors for delaying the progression of chronic kidney disease (CKD)and blood pressure in persons with uncontrolled hypertension. The experiment was divided into 2 periods: the control period (week 1-6) and the intervention period (week 7-12). In the control period, the sample received regular care, and in the intervention period, they received the motivational interviewing and self-management support program. A sample of 32 participants were purposively selected from persons with uncontrolled hypertension and CKD stage 1–2. The data were analyzed using one-way repeated measures ANOVA and pairwise comparisons with Bonferroni correction to compare mean scores at the end of 6th week and 12th week. The results revealed that mean score of behaviors for delaying the progression of chronic kidney disease after intervention was significantly higher than that before intervention.The average blood pressure levels after intervention was significantly lower than that before experiment. The results indicated that the motivation interviewing and self-management support program could increase behaviors for delaying the progression of chronic kidney disease and reduce blood pressure among persons with uncontrolled hypertension. Keywords: Motivation interviewing, Self-management support, Behaviors for delaying the progression of chronic kidney disease, Blood pressure, Hypertension